Impact of Green Growth Factors on Foreign Direct Investment: Evidence from Central Asia - Ilyas, Assel; Myrzatay, Yerzhan; Umirzakov, Samazhan; Baimukhanova, Sariya; Kakizhanova, Tolkyn (International Journal of Energy Economics and Policy, 2025)
One of the pressing issues in developing countries with abundant mineral resources is the impact of foreign investment on economic development without harming the environment. The purpose of this research is to assess the impact of CO2 emissions from Industrial Processes, electricity production oil, gas and coal sources, and Oil price indicators, among the green growth factors, on foreign direct investment in Central Asian countries (Kazakhstan, the Kyrgyz Republic, and Uzbekistan). For this purpose, statistical data for the period 1998-2023 were obtained from the World Data Bank database. The pooled mean group-autoregressive distributed lag (PMG-ARDL) methodology was applied. The model results showed the cumulative impact of these factors for Central Asia. When testing the model for each country separately, a statistically significant impact of the factors was revealed. Since all three countries are sufficiently rich in natural resources, priority should be given not only to effectively develop mineral resources, but also to minimize damage to nature and protect it. In this regard, the authors shared a number of recommendations in the concluding section.